ZnO nanoparticles and compositional dependence of structural, thermal, mechanical and electrical properties of eutectic SAC355 lead-free solder - Al-Sorory, Hamed; Gumaan, Mohammed S.; Shalaby, Rizk Mostafa (Emerald Publishing Limited, 2022)
Purpose This paper aims to summarise the effects of ZnO nanoparticles (0.1, 0.3, 0.5, 0.7 and 1.0 Wt.%) on the structure, mechanical, electrical and thermal stability of Sn-3.5Ag-0.5Cu (SAC355) solder alloys for high-performance applications. Design/methodology/approach The phase identification and morphology of the solders were studied using X-ray diffraction and scanning electron microscopy. Thermal parameters were investigated using differential scanning calorimetry. The elastic parameters such as Young's modulus (E) and internal friction (Q?1) were investigated using the dynamic resonance technique, whereas the Vickers hardness (Hv) and creep indentation (n) were examined using a Vickers microhardness tester. Findings Microstructural analysis revealed that ZnO nanoparticles (NPs) were distributed uniformly throughout the Sn matrix. Furthermore, addition of 0.1, 0.3 and 0.7?Wt.% of ZnO NPs to the eutectic (SAC355) prevented crystallite size reduction, which increased the strength of the solder alloy. Mechanical parameters such as Young's modulus improved significantly at 0.1, 0.3 and 0.7?Wt.% ZnO NP contents compared to the ZnO-free alloy. This variation can be understood by considering the plastic deformation. The Vickers hardness value (Hv) increased to its maximum as the ZnO NP content increased to 0.5. A stress exponent value (n) of approximately two in most composite solder alloys suggested that grain boundary sliding was the dominant mechanism in this system. The electrical resistance (?) increased its maximum value at 0.5?Wt.% ZnO NPs content. The addition of ZnO NPs to plain (SAC355) solder alloys increased the melting temperature (Tm) by a few degrees. Originality/value Development of eutectic (SAC355) lead-free solder doped with ZnO NPs use for electronic packaging.